2014
DOI: 10.4014/jmb.1402.02013
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacteriophages Infecting Xanthomonas oryzae pv. oryzae in Paddy Fields and Its Potential to Control Bacterial Leaf Blight of Rice

Abstract: Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo) is a very serious disease in rice-growing regions of the world. In spite of their economic importance, there are no effective ways of protecting rice plants from this disease. Bacteriophages infecting Xoo affect the population dynamics of the pathogen and consequently the occurrence of the disease. In this study, we investigated the diversity, host range, and infectivity of Xoo phages, and their use as a bicontrol agent on BLB was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…In addition, DNA methylation is one of the known antiviral mechanisms of bacteria (Labrie et al, 2010). Within the same bacterial species, different strains show distinct resistant patterns against infection of diverse bacteriophages (Chae et al, 2014). Host ranges of bacteriophages are most likely determined by specific DNA methyltransferases in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, DNA methylation is one of the known antiviral mechanisms of bacteria (Labrie et al, 2010). Within the same bacterial species, different strains show distinct resistant patterns against infection of diverse bacteriophages (Chae et al, 2014). Host ranges of bacteriophages are most likely determined by specific DNA methyltransferases in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…and Dickeya sp. (Evans et al, 1979 ; Sharp et al, 1986 ; Lynch et al, 2012 ; Chae et al, 2014 ; Santamaría et al, 2014 ; Czajkowski et al, 2015 ). For this approach, elimination of pathogens and reduction of soil bacterial species that directly compete with the biocontrol agents (i.e., those sharing similar metabolic capacities) are desirable.…”
Section: Creating Microhabitats For Host Beneficial Bacteria By Intromentioning
confidence: 99%
“…observed that the abundance of virus-like particles (VLPs) in paddy floodwaters during the rice cultivation period ranged from 5.6 × 10 6 to 1.2 × 10 9  VLPs·mL −1 with a mean of 1.5 × 10 8  VLPs·mL −1 , which was greater than the number of viruses in oceans and estuaries1617. Chae et al 18. isolated 34 phages infecting Xanthomonas oryzae pv.…”
mentioning
confidence: 99%